A method for recycling preparation of battery-grade lithium carbonate and iron phosphate by using waste lithium iron phosphate batteries

CN118495566BActive Publication Date: 2026-11-03YICHANG BRUNP RECYCLING TECH CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410601489.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-15
Publication Date
2026-11-03
Estimated Expiration
2044-05-15

AI Technical Summary

Technical Problem

In the current technology for recycling waste lithium iron phosphate batteries, it is difficult to effectively remove aluminum and copper impurities, which affects the electrochemical performance of the positive electrode material of lithium iron phosphate batteries. Furthermore, traditional impurity removal methods are inefficient and costly, making it difficult to achieve the purity and yield requirements of battery-grade lithium iron phosphate.

Method used

Battery-grade lithium carbonate is prepared by magnetic separation, crushing, and screening of the positive electrode sheets of waste lithium iron phosphate batteries, followed by pulping, acid leaching, and oxidation. Copper is removed by chelating resin, aluminum and iron are removed by alkaline precipitation, and battery-grade lithium carbonate is prepared by MVR evaporation and crystallization. Battery-grade iron phosphate is prepared by mixing iron phosphate slag with secondary iron slag, removing impurities by acid leaching, and then calcining.

Benefits of technology

It achieves efficient recovery of lithium resources, with a lithium resource utilization rate of 99.3% and iron and phosphorus resource recovery rates of 95% respectively. The prepared lithium carbonate and iron phosphate products meet battery-grade standards, reducing the difficulty and loss of pretreatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118495566B_ABST
    Figure CN118495566B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of battery recycling and reuse, and particularly relates to a method for recycling and preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries, comprising the following steps: (1) disassembling and separating the discharged recovered waste lithium iron phosphate batteries to obtain positive electrode sheets, negative electrode sheets, separators and shells, and then magnetically separating, crushing and screening the obtained positive electrode sheets to obtain electrode sheet powder; (2) after slurry preparation, acid leaching and oxidation, and washing and pressure filtration, a filtrate and a phosphorus-iron residue are obtained; (3) after sequentially removing copper, aluminum and iron from the filtrate, a lithium-containing post-liquid and secondary iron residue are obtained, and the lithium-containing post-liquid is added into a basic additive for reaction, and then battery-grade lithium carbonate is obtained through MVR evaporation crystallization; (4) after mixing the phosphorus-iron residue and the secondary iron residue and acid leaching to remove impurities, a post-impurity-removal liquid is obtained, and then acid, an oxidizing agent and a surfactant are added into the post-impurity-removal liquid for reaction, and then the obtained slurry is washed and pressure filtered, calcined and de-magnetized to obtain battery-grade iron phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery recycling technology, and specifically relates to a method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries. Background Technology

[0002] With increasing global awareness of environmental protection and the depletion of traditional energy resources, the search for renewable and clean energy has become an inevitable trend. Lithium-ion batteries, as a new type of energy storage device, have received widespread attention in fields such as new energy vehicle power batteries, electrochemical energy storage, and 3C digital products. Among them, lithium iron phosphate (LFP) batteries have gained widespread recognition due to their excellent thermal stability, outstanding cycle performance, non-toxic properties, and cost-effectiveness. However, the widespread use of LFP batteries has led to a surge in the demand for waste LFP battery disposal. Poor management of waste LFP batteries can have adverse consequences, including environmental degradation and pollution of valuable secondary resources. The recycling of waste LFP batteries is not only crucial for reducing environmental pollution caused by harmful components but also enables the effective recovery of valuable components, promoting resource recycling. This, in turn, is conducive to the sustainable development of the energy industry, promotes economic benefits, and stimulates social development. Therefore, the recycling of waste LFP batteries is necessary and must be consistently implemented.

[0003] Currently, the main processes for recovering high-value elements from spent lithium iron phosphate batteries include wet leaching and solid-phase high-temperature calcination regeneration of lithium iron phosphate. The wet leaching process involves roasting and crushing spent batteries to obtain a mixture, then removing impurities such as copper and aluminum to obtain a mixed iron and lithium slag. Iron and lithium elements are then leached simultaneously, followed by selective precipitation to obtain lithium products. The iron-phosphate slag is treated as general solid waste. Because lithium is a scarce resource, current recycling processes for spent lithium iron phosphate batteries focus only on lithium recovery, neglecting the recycling and treatment of the iron-phosphate slag. Furthermore, the phosphorus slag produced during the recycling of common waste lithium iron phosphate batteries generally contains high levels of Al and Cu impurities due to the conductive materials in the batteries. Since Al and Cu have similar properties to Fe, they are difficult to separate. The presence of these impurities will affect the recycling of such phosphorus slag to prepare battery-grade iron phosphate, thus affecting the electrochemical performance of lithium iron phosphate battery cathode materials. Currently, methods for removing aluminum and copper impurities include using alkali leaching, but the impurity content in the iron phosphate recycled by this method still does not meet the application standards for battery-grade iron phosphate. Other methods use acidic solutions for purification, but these are either complex, inefficient, and have poor purification effects, or they are costly and ineffective, resulting in low purity and yield of the obtained iron phosphate product. Summary of the Invention

[0004] This invention aims to address at least one of the technical problems existing in related technologies. To this end, this invention proposes a method for preparing battery-grade lithium carbonate and iron phosphate from recycled waste lithium iron phosphate batteries. This method boasts high resource recycling efficiency and produces products with excellent performance indicators, providing a solid foundation for the efficient recycling of waste batteries.

[0005] The above-mentioned technical objective of the present invention is achieved through the following technical solution:

[0006] A method for preparing battery-grade lithium carbonate and iron phosphate by recycling waste lithium iron phosphate batteries includes the following steps: (1) discharging and separating the recycled waste lithium iron phosphate batteries to obtain positive electrode, negative electrode, separator and shell, and magnetically separating, crushing and screening the obtained positive electrode to obtain electrode powder; (2) slurrying the electrode powder obtained in step (1), acid leaching and oxidation, washing and pressing and filtering to obtain filtrate and iron phosphate slag; (3) removing copper, aluminum and iron from the filtrate obtained in step (2) to obtain lithium-containing liquid and secondary iron slag, adding alkaline additives to the obtained lithium-containing liquid and reacting, and then evaporating and crystallizing by MVR to obtain battery-grade lithium carbonate; (4) mixing the iron phosphate slag obtained in step (2) and the secondary iron slag obtained in step (3) and acid leaching to remove impurities to obtain impurity-removed liquid, adding acid, oxidant and surfactant to the impurity-removed liquid and reacting, and then washing, pressing and filtering, calcining and demagnetizing the obtained slurry to obtain battery-grade iron phosphate.

[0007] In one embodiment, in step (1), the discharge is performed by immersing the recycled waste lithium iron phosphate battery in a discharge salt solution, wherein the discharge salt solution is either a sodium chloride solution or a potassium chloride solution, and the discharge time is 24h-48h.

[0008] In one embodiment, in step (1), the crushing method includes high-temperature calcination and physical crushing and air separation. The high-temperature calcination method involves calcining the positive electrode sheet at a high temperature of 300-750℃ to decompose the binder, then completely dissolving the current collector aluminum foil with an excess alkaline solution, washing and separating the solid and liquid phases, drying the solid phase and then pulverizing it into powder. The physical crushing and air separation method involves first removing iron from the positive electrode sheet through magnetic separation, then continuously crushing it with hammers and separating it with cyclones to obtain electrode powder and aluminum powder respectively.

[0009] In one embodiment, in step (2), the pulping refers to mixing the electrode powder with a sodium chloride solution or a potassium chloride solution at a weight ratio of 1:(4-6).

[0010] In one embodiment, in step (2), the pulping refers to mixing the electrode powder with a sodium chloride solution or a potassium chloride solution at a weight ratio of 1:(4.5-5.5). The mass concentration of the sodium chloride solution or potassium chloride solution used is 8%-10%.

[0011] In one embodiment, in step (2), the acidic solution used for acid leaching oxidation is one of dilute sulfuric acid, dilute hydrochloric acid, and dilute nitric acid.

[0012] In one embodiment, in step (2), the oxidant used in the acid leaching oxidation is one of hydrogen peroxide or ammonium persulfate.

[0013] In one embodiment, in step (2), the oxidant used in the acid leaching oxidation reacts with the Fe in the electrode powder. 2+ The molar ratio is (0.5-1.5):1.

[0014] In one embodiment, in step (2), the oxidant reacts with the Fe in the electrode powder. 2+ The molar ratio is (0.75-1.25):1.

[0015] In one embodiment, in step (2), the acid leaching oxidation reaction temperature is 50-90°C and the reaction time is 2-3 hours.

[0016] In one embodiment, in step (2), the reaction temperature of the acid leaching oxidation is 60-85°C and the reaction time is 2-3 hours.

[0017] In one embodiment, in step (3), the copper removal method is at least one of resin copper removal, complexation copper removal, and iron powder copper removal.

[0018] In one embodiment, the copper removal method using resin involves using a chelating ion exchange resin to perform multi-stage countercurrent static adsorption on the filtrate, thereby reducing the copper ion concentration in the filtrate to below the standard value.

[0019] In one embodiment, the chelating ion exchange resin is at least one of Purolite S930plus chelating resin, Lanxess TP207 chelating resin, D401 chelating resin, and KF340 copper removal resin.

[0020] In one embodiment, the copper removal method involves heating the filtrate, keeping it at that temperature and stirring, then adding a complexing agent, and using the complexation reaction to precipitate and remove copper.

[0021] In one embodiment, the complexing agent is at least one selected from EDTA, citric acid, and oxalic acid. EDTA refers to ethylenediaminetetraacetic acid.

[0022] In one embodiment, the iron powder copper removal method involves adding an excess of iron powder to the filtrate and removing copper through a displacement reaction by utilizing the difference in chemical reactivity.

[0023] In one embodiment, in step (3), the method for removing aluminum involves adding an alkaline substance to the filtrate after copper removal to precipitate and remove aluminum. After adding the alkaline substance, the pH of the filtrate after copper removal is adjusted to 3.5-4.0. In one embodiment, the alkaline substance is at least one of sodium bicarbonate, sodium carbonate, or sodium hydroxide.

[0024] In one embodiment, in step (3), the method for removing iron is to add hydrogen peroxide and liquid alkali to the filtrate after aluminum removal to adjust the pH of the solution to 4.0-4.5, and then precipitate to remove iron.

[0025] In one embodiment, in step (3), the alkaline additive is at least one of sodium hydroxide, sodium carbonate, potassium carbonate and lithium carbonate.

[0026] In one embodiment, in step (4), the acid added to the purified solution is at least one of concentrated phosphoric acid, concentrated sulfuric acid and concentrated hydrochloric acid.

[0027] In one embodiment, in step (4), the oxidant is one of hydrogen peroxide and ammonium persulfate.

[0028] In one embodiment, in step (4), the surfactant is one of EDTA, CTAB and SDS, and the amount of surfactant added is 5%-15% of the mass of iron in the purified liquid. EDTA refers to ethylenediaminetetraacetic acid, CTAB refers to hexadecyltrimethylammonium bromide, and SDS refers to sodium dodecyl sulfate.

[0029] In one embodiment, in step (4), the calcination temperature is 550-750°C and the calcination time is 6-10 hours.

[0030] In one embodiment, in step (4), the calcination temperature is 550-650°C and the calcination time is 6-9 hours.

[0031] The beneficial effects of this invention are:

[0032] (1) During the crushing of the positive electrode sheet, the present invention can remove most of the aluminum slag in the waste lithium iron phosphate battery by screening and demagnetizing, and collect it by crushing, which greatly reduces the difficulty and loss of battery pretreatment and improves the recycling and reuse of energy resources.

[0033] (2) Compared with traditional waste lithium iron phosphate battery recycling, the present invention re-acid-leached and uniformly mixed the phosphorus iron slag, which is treated as solid waste in traditional recycling, with the secondary iron slag obtained in the lithium extraction process, and used it as raw material for synthesizing battery-grade iron phosphate. The iron phosphate prepared by recycling fully meets the characteristics of battery-grade iron phosphate, which greatly improves the recycling and reuse of phosphorus and iron resources.

[0034] In summary, compared with existing technologies, the present invention, after obtaining the solution from the acid hydrolysis of the positive electrode, performs impurity removal and lithium extraction to prepare battery-grade lithium carbonate. The secondary iron slag obtained during the lithium extraction process is mixed with the pre-process phosphorus iron slag as raw material to synthesize iron phosphate. Following the concept of full resource recovery, the invention expands into two product lines: battery-grade lithium carbonate and battery-grade iron phosphate. The obtained lithium carbonate and iron phosphate products meet battery-grade standards. Furthermore, by controlling the process operation at each stage, the lithium resource recovery rate can reach 99.3%, the iron resource recovery efficiency can reach 95%, and the phosphorus resource recovery rate can also reach 95% in the entire production line. Attached Figure Description

[0035] Figure 1 This is a flowchart illustrating Embodiment 1 of the present invention;

[0036] Figure 2 This is a SEM image of the battery-grade lithium carbonate prepared in Example 1 of the present invention;

[0037] Figure 3 This is a SEM image of the battery-grade iron phosphate prepared in Example 1 of the present invention;

[0038] Figure 4 The image shows the XRD pattern of the battery-grade iron phosphate prepared in Example 1 of this invention. Detailed Implementation

[0039] The present invention will be further described below with reference to specific embodiments.

[0040] Example 1:

[0041] A method for preparing battery-grade lithium carbonate and iron phosphate from recycled waste lithium iron phosphate batteries, such as... Figure 1 As shown, it includes the following steps:

[0042] (1) The recycled waste lithium iron phosphate batteries are fully immersed in sodium chloride solution and discharged for 24 hours. Then, the positive electrode, negative electrode, separator and shell are obtained by mechanical physical crushing and disassembly. The waste lithium iron phosphate positive electrode is then transported by belt conveyor magnetic separation to remove iron before entering the mechanical crusher for multiple hammer crushing and cyclone separation to obtain electrode powder and aluminum powder respectively.

[0043] (2) Add the electrode powder to a 10% sodium chloride solution, with a weight ratio of electrode powder to sodium chloride solution of 1:4. Stir thoroughly to obtain an electrode powder slurry, and then take samples to test the Fe content in the electrode powder. 2+ Concentration: Add an appropriate amount of dilute sulfuric acid solution and a slight excess of hydrogen peroxide to the slurry. The hydrogen peroxide in the hydrogen peroxide reacts with the Fe in the electrode powder. 2+The molar ratio was 0.75:1, the reaction temperature was controlled at 50℃, and the reaction time was 3h. After the oxidation reaction was carried out for a period of time, the mixture was thoroughly washed and filtered to obtain the filtrate and phosphorus iron slag.

[0044] (3) The filtrate obtained in step (2) is subjected to copper removal by adding a copper-removing chelating ion exchange resin, Purolite S930plus. The copper ions are adsorbed by functional genes on the resin surface to form complexes, thereby reducing the copper ion concentration in the solution and removing copper. Sodium bicarbonate is added to adjust the pH of the solution to 3.7 for precipitation to remove aluminum. An appropriate amount of 27.5% hydrogen peroxide and liquid alkali are added to adjust the pH of the solution to 4.0 for precipitation to remove iron. After solid-liquid separation, lithium-containing post-liquid and secondary iron slag are obtained. The lithium ion concentration in the lithium-containing post-liquid is sampled and a slightly excess of sodium carbonate (molar ratio of sodium carbonate to lithium ions = 1.05:1) is added to the lithium-containing post-liquid for full reaction. Finally, after MVR evaporation and crystallization, battery-grade lithium carbonate is prepared. The SEM image of the prepared battery-grade lithium carbonate is shown in the figure. Figure 2 As shown, lithium carbonate nanoparticles with good uniformity were prepared.

[0045] (4) Collect the ferrophosphate slag obtained in step (2) and the secondary slag obtained in step (3) together as ferrophosphate slag. After acid leaching to remove impurities three times, the purified solution is obtained. Then, samples are taken to test the Fe content in the purified solution. 2+ After the impurity-removing filter residue was washed, dried, and collected, graphite slag was obtained. An appropriate amount of concentrated phosphoric acid, hydrogen peroxide, and a suitable amount of CTAB surfactant were added to the purified liquid for oxidative synthesis. The mass of the added CTAB surfactant was 5% of the iron mass in the purified liquid. The slurry was then subjected to washing, pressure filtration, flash drying, calcination at 550℃ in a rotary kiln for 10 hours, grinding, sieving, and demagnetization to finally obtain battery-grade iron phosphate. The SEM image of the prepared battery-grade iron phosphate is shown below. Figure 3 As shown, the XRD pattern of the prepared battery-grade iron phosphate exhibits a relatively uniform micron-sized flake-like structure. Figure 4 As shown, Figure 4 Fully compatible with battery-grade iron phosphate standard card: JCPDs: 77-0094.

[0046] Example 2:

[0047] A method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries includes the following steps:

[0048] (1) The recycled waste lithium iron phosphate batteries were fully immersed in potassium chloride solution and discharged for 48 hours. Then, the positive electrode, negative electrode, separator and shell were obtained by mechanical physical crushing and disassembly. Then, the powder was made by high temperature calcination. Specifically, the binder was decomposed by calcination at 500℃, the current collector aluminum foil was completely dissolved by excess sodium hydroxide solution, the solid and liquid were separated after cleaning, and finally the powder was dried and crushed to obtain electrode powder.

[0049] (2) Add the electrode powder to a 10% sodium chloride solution, with a weight ratio of electrode powder to sodium chloride solution of 1:4. Stir thoroughly to obtain an electrode powder slurry, and then take samples to test the Fe content in the electrode powder. 2+ Concentration: Add an appropriate amount of dilute sulfuric acid and dilute hydrochloric acid mixed solution to the slurry, and add a slight excess of ammonium persulfate solution. The ammonium sulfate in the ammonium sulfate solution reacts with the Fe in the electrode powder. 2+ The molar ratio was 1.25:1, the reaction temperature was controlled at 90℃, and the reaction time was 2h. After the oxidation reaction was carried out for a period of time, the mixture was thoroughly washed and filtered to obtain the filtrate and phosphorus iron slag.

[0050] (3) Add excess iron powder to the filtrate prepared in step (2) to replace copper, add sodium carbonate to adjust the pH of the solution to 3.7 and precipitate to remove aluminum, add appropriate amount of 27.5% hydrogen peroxide and liquid alkali to adjust the pH of the solution to 4.0 and precipitate to remove iron. After solid-liquid separation, lithium-containing liquid and secondary iron slag are obtained. Take a sample to detect the lithium ion concentration in the lithium-containing liquid and add a slightly excess sodium hydroxide (molar ratio of sodium hydroxide: lithium ion = 1.05:1) to the lithium-containing liquid to react fully. Finally, after MVR evaporation and crystallization, battery-grade lithium carbonate is prepared.

[0051] (4) Collect the ferrophosphate slag obtained in step (2) and the secondary slag obtained in step (3) together as ferrophosphate slag. After acid leaching to remove impurities three times, take samples to test the Fe content in the leaching solution. 2+ After the impurity-removed filter residue is washed, dried, and collected, graphite slag is obtained. An appropriate amount of concentrated phosphoric acid, hydrogen peroxide, and EDTA surfactant are added to the purified liquid for oxidative synthesis. The mass of the added EDTA surfactant is 10% of the mass of iron in the purified liquid. The slurry is then subjected to washing, pressure filtration, flash drying, calcination at 750℃ in a rotary kiln for 6 hours, grinding, sieving, and demagnetization to finally obtain battery-grade iron phosphate.

[0052] Example 3:

[0053] A method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries includes the following steps:

[0054] (1) The recycled waste lithium iron phosphate batteries are fully immersed in sodium chloride solution and discharged for 36 hours. Then, the positive electrode, negative electrode, separator and shell are obtained by mechanical physical crushing and disassembly. The waste lithium iron phosphate positive electrode is then transported by belt conveyor magnetic separation to remove iron before entering the mechanical crusher for multiple hammer crushing and cyclone separation to obtain electrode powder and aluminum powder respectively.

[0055] (2) Add the electrode powder to a 10% sodium chloride solution, with a weight ratio of electrode powder to sodium chloride solution of 1:4. Stir thoroughly to obtain an electrode powder slurry, and then take samples to test the Fe content in the electrode powder. 2+Concentration: Add an appropriate amount of dilute sulfuric acid and dilute hydrochloric acid mixed solution to the slurry, and add a slight excess of hydrogen peroxide. The hydrogen peroxide in the hydrogen peroxide reacts with the Fe in the electrode powder. 2+ The molar ratio was 1:1, the reaction temperature was controlled at 80℃, and the time was 2.5h. After the oxidation reaction was carried out for a period of time, the mixture was thoroughly washed and filtered to obtain the filtrate and phosphorus iron slag.

[0056] (3) The filtrate obtained in step (2) is subjected to copper removal by adding a mixture of chelating ion exchange resin Lanxess TP207 chelating resin and D401 chelating resin, sodium carbonate and sodium bicarbonate are added to adjust the pH of the solution to 3.7, aluminum is removed by precipitation, and an appropriate amount of 27.5% hydrogen peroxide and liquid alkali are added to adjust the pH of the solution to 4.0 to remove iron by precipitation. After solid-liquid separation, lithium-containing post-liquid and secondary iron slag are obtained. The lithium ion concentration in the lithium-containing post-liquid is sampled and a slightly excess amount of potassium carbonate (molar ratio of potassium carbonate: lithium ion = 1.05:1) is added to the lithium-containing post-liquid to allow it to react fully. Finally, battery-grade lithium carbonate is prepared by MVR evaporation and crystallization.

[0057] (4) Collect the ferrophosphate slag obtained in step (2) and the secondary slag obtained in step (3) together as ferrophosphate slag. After acid leaching to remove impurities three times, take samples to test the Fe content in the leaching solution. 2+ After the impurity-removed filter residue is washed, dried, and collected, graphite slag is obtained. An appropriate amount of concentrated phosphoric acid and concentrated sulfuric acid mixed solution, hydrogen peroxide, and an appropriate amount of CTAB surfactant are added to the impurity-removed liquid for oxidative synthesis. The mass of the added CTAB surfactant is 15% of the mass of iron in the impurity-removed liquid. The slurry is then subjected to washing, pressure filtration, flash drying, calcination at 600℃ in a rotary kiln for 8 hours, grinding, sieving, and demagnetization to finally obtain battery-grade iron phosphate.

[0058] Example 4:

[0059] A method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries includes the following steps:

[0060] (1) The recycled waste lithium iron phosphate batteries are fully immersed in sodium chloride solution and discharged for 36 hours. Then, the positive electrode, negative electrode, separator and shell are obtained by mechanical physical crushing and disassembly. The waste lithium iron phosphate positive electrode is then transported by belt conveyor magnetic separation to remove iron before entering the mechanical crusher for multiple hammer crushing and cyclone separation to obtain electrode powder and aluminum powder respectively.

[0061] (2) Add the electrode powder to a 10% sodium chloride solution, with a weight ratio of electrode powder to sodium chloride solution of 1:4. Stir thoroughly to obtain an electrode powder slurry, and then take samples to test the Fe content in the electrode powder. 2+ Concentration: Add an appropriate amount of dilute sulfuric acid and dilute hydrochloric acid mixed solution to the slurry, and add a slight excess of hydrogen peroxide. The hydrogen peroxide in the hydrogen peroxide reacts with the Fe in the electrode powder. 2+The molar ratio was 1:1, the reaction temperature was controlled at 80℃, and the time was 2.5h. After the oxidation reaction was carried out for a period of time, the mixture was thoroughly washed and filtered to obtain the filtrate and phosphorus iron slag.

[0062] (3) The filtrate obtained in step (2) is subjected to copper removal by adding a mixture of chelating ion exchange resin Lanxess TP207 chelating resin and D401 chelating resin. After adding sodium carbonate and sodium bicarbonate to adjust the pH of the solution to 3.0, aluminum is removed by precipitation. After adding an appropriate amount of 27.5% hydrogen peroxide and liquid alkali to adjust the pH of the solution to 3.5, iron is removed by precipitation. After solid-liquid separation, lithium-containing post-liquid and secondary iron slag are obtained. The lithium ion concentration in the lithium-containing post-liquid is sampled and an appropriate amount of potassium carbonate (molar ratio of potassium carbonate: lithium ion = 1.05:1) is added to the lithium-containing post-liquid to allow it to react fully. Finally, after MVR evaporation and crystallization, battery-grade lithium carbonate is prepared.

[0063] (4) Collect the ferrophosphate slag obtained in step (2) and the secondary slag obtained in step (3) together as ferrophosphate slag. After acid leaching to remove impurities three times, take samples to test the Fe content in the leaching solution. 2+ After the impurity-removed filter residue is washed, dried, and collected, graphite slag is obtained. An appropriate amount of concentrated phosphoric acid and concentrated sulfuric acid mixed solution, hydrogen peroxide, and an appropriate amount of CTAB surfactant are added to the impurity-removed liquid for oxidative synthesis. The mass of the added CTAB surfactant is 15% of the mass of iron in the impurity-removed liquid. The slurry is then subjected to washing, pressure filtration, flash drying, calcination at 600℃ in a rotary kiln for 8 hours, grinding, sieving, and demagnetization to finally obtain battery-grade iron phosphate.

[0064] Test example:

[0065] The components of the iron phosphate products prepared in Examples 1-4 were analyzed, and the results are shown in Table 1. The components of the lithium carbonate products prepared in Examples 1-4 were analyzed, and the results are shown in Table 2.

[0066] Table 1: Results of Ferric Phosphate Composition Test

[0067]

[0068] Table 2: Lithium carbonate composition test results

[0069]

[0070]

[0071] As shown in Tables 1 and 2, the method of preparing battery-grade lithium carbonate and lithium iron phosphate by recycling waste lithium iron phosphate batteries in this invention meets the technical requirements for battery-grade anhydrous lithium iron phosphate and lithium carbonate.

Claims

1. A method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries, characterized in that: Includes the following steps: (1) Discharge the recycled waste lithium iron phosphate batteries and disassemble them to obtain positive electrode, negative electrode, separator and shell. The obtained positive electrode is magnetically separated, crushed and screened to obtain electrode powder. (2) After the electrode powder obtained in step (1) is slurried, acid-leached and oxidized, washed and filtered to obtain filtrate and phosphorus iron slag; (3) After removing copper, aluminum and iron from the filtrate prepared in step (2) in sequence, lithium-containing post-liquid and secondary iron slag are obtained. After adding alkaline additives to the lithium-containing post-liquid and reacting, battery-grade lithium carbonate is obtained by MVR evaporation and crystallization. (4) The phosphorus iron slag obtained in step (2) and the secondary iron slag obtained in step (3) are mixed and acid-leached to remove impurities to obtain a purified liquid. Acid, oxidant and surfactant are added to the purified liquid and reacted. The resulting slurry is washed, filtered, calcined and demagnetized to obtain battery-grade iron phosphate. In step (3), the alkaline additive is at least one of sodium carbonate, potassium carbonate and lithium carbonate. In step (4), the surfactant is CTAB. The amount of surfactant added is 5%-15% of the iron mass in the purified liquid. The calcination temperature is 550-650℃ and the calcination time is 6-9h. The battery-grade iron phosphate has a micron flake structure.

2. The method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (2), the pulping refers to mixing the electrode powder with sodium chloride solution or potassium chloride solution at a weight ratio of 1:(4-6).

3. The method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (2), the oxidant used in the acid leaching oxidation reacts with the Fe in the electrode powder. 2+ The molar ratio is (0.5-1.5):

1.

4. The method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (2), the reaction temperature of the acid leaching oxidation is 50-90℃ and the reaction time is 2-3h.

5. The method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (3), the copper removal method is at least one of resin copper removal, complexation copper removal and iron powder copper removal.

6. The method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries according to claim 5, characterized in that: The copper removal method involves heating the filtrate, keeping it at that temperature and stirring, then adding a complexing agent, and using the complexation reaction to precipitate and remove copper.

7. The method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries according to claim 5, characterized in that: The iron powder copper removal method involves adding an excess of iron powder to the filtrate to remove copper through a displacement reaction.

8. The method for preparing battery-grade lithium carbonate and iron phosphate from waste lithium iron phosphate batteries according to claim 1, characterized in that: In step (3), the method used to remove aluminum is to add an alkaline substance to the filtrate after copper removal to precipitate and remove aluminum.

Citation Information

Patent Citations

  • Method used for producing ferric phosphate from yellow phosphorus by-product phosphor iron slag

    CN108101014A

  • Method for preparing lithium iron phosphate positive electrode material from waste lithium iron phosphate battery

    CN111009660A

  • Method for wet recovery of iron phosphate and lithium carbonate from lithium iron phosphate battery

    CN117361467A

  • Lithium iron phosphate battery positive electrode material recovery method

    CN117913406A